Malaysians and their identities - Yeoh, Seng Guan (Strategic Information and Research Development Centre, 2017)
Malaysians and their Identities presents a kaleidoscope of insights based on original empirical research by young Malaysian scholars. Among others, their topics cover festive TV advertisements, connoisseur café culture, the smartphone, online sports gaming, Islamic fashion, women indie musicians, men's health magazines, inter-racial marriages, and friendships in private universities.